Correlation of High Fluorescence Lymphocyte Count and Thrombocytopenia in Dengue Fever Infection - Ileandea, Brigita Vania; Nurhayati, Dewi; Sunardi, Agus; Hikam, Muhamad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Dengue fever is a disease with mosquitos as vectors that carry one of four types of viruses (DENV -1, -2, -3, and -4). Dengue infects almost 2.5 million people throughout the world. Based on the latest WHO classification, it carries an extensive range of symptoms and severity. High Fluorescence Lymphocyte Count (HFLC) is a simple hematological parameter that calculates the amount of nucleic acid in ribonucleic acid or RNA in reactive lymphocytes. Lymphocyte reactions in patients with dengue virus infection give rise to this study, suggesting that HFLC can predict the severity of thrombocytopenia. This research was an observational analytical study with a cross-sectional design. This study aims to look at HFLC as an indicator of the seriousness of platelet counts in dengue fever patients. There was no significant relationship between HFLC values and thrombocytopenia in the children with dengue infection (p=0.496). In the adult group, there was a significant relationship between HFLC and thrombocytopenia (p=0.002). The Receiver Operating Characteristic (ROC) curve for HFLC as a predictor of severe thrombocytopenia in an adult group showed an HFLC cut-off of 5.35, sensitivity of 56.8%, and specificity of 58.5%. In conclusion, a significant relationship was found between HFLC values and thrombocytopenia in the adult group with dengue fever.